The Acoustic Impact on the Application of (Al-Khafd Alal Jawar) - Mudhafer Abd Roomi , Assist. Prof. Dr. (lark, 2023)
This research addresses the issue of the concept known as "Al-Khafd Alal Jawar" in the works of grammarians. The term "Al-Jarru ’ala Al-Mujawarah" refers to the grammatical phenomenon of a delayed movement of a word following a preceding word due to adjacency. The research discusses this phenomenon through the following aspects: conditions and criteria for "Al-Khafd Alal Jawar," variations among grammarians regarding "Al-Khafd Alal Jawar," and its occurrence in the Holy Quran. The research concludes with an analysis to determine the cause of this phenomenon. It finds that it is purely a phonetic reason, as language naturally tends to favor ease and simplicity. Therefore, words are influenced by each other due to adjacency, merely based on the pleasantness of their pronunciation without necessarily being semantically related. Arabic speakers, like any speaker, blend their thoughts with their speech and go with the flow at the speed allowed by their linguistic proficiency. Sounds, including movements, differ in intensity, and a weak sound can be influenced by an easier and smoother sound that follows, whether it is in immediate or non-immediate adjacency.